Kopcovité útvary z hlíny a kamene jako prostredek k vymezení hranic území v písemných pramenech kláštera Hradisko u Olomouce - Novák, Jakub (Archaeologia historica, 2020)
Keywords: hradisko

Kopcovité útvary z hlíny a kamene jako prostredek k vymezení hranic území v písemných pramenech kláštera Hradisko u Olomouce - Novák, Jakub (Archaeologia historica, 2020)
Keywords: hradisko

Klášter Hradiště ve sporu o domašovský les. Příspěvek k dějinám mezního práva ve středověku - Razim, Jakub (Právněhistorické studie, 2020)
In a survey into the legal history of the Premonstratensian monastery Hradiště near Olomouc, in which I tried to uncover the details of the border dispute over church land near Domašov around 1220, I placed under a microscope the forged document CDB II 376, which is the result of numerous counterfeiting activities taking place in Hradiště scriptorium since the second half of the 13th century. The diplomatic material of the ancient Moravian foundation has been an interesting subject of investigation both because it is famous for its verbosity, with which it describes legal realities, and because the monastery, as a colonizer, had constantly been involved in conflicts with the surrounding landowners making its destiny an excellent springboard for the research of the Law of Borders in the Middle Ages. However, in order to shed light on one of the long-neglected aspects of medieval legal life that I encounter here, it was necessary to test the factual accuracy of CDB II 376. A comparison with chartes and records on the practices of the Law of Borders, which have been preserved in our region since the Přemyslid period, was chosen as a tool of source criticism. The findings I have reached lead to the conclusion that the forgery fits well into our general knowledge of public administration in the first decades of the 13th century. After all, the justification of the territorial aspirations substantiated in writing had to be acknowledged also by the opponent of the Premonstratensian monastery, Albert of Šternberk.
Keywords: hradisko